Ultrastructure of the muscular membrane of the mice gallbladder wall under the influence of ursodeoxycholic acid - A.E. Abaturov; V.L. Babуch; I.V. Tverdokhlib (Zaslavsky O.Yu., 2024)
Background. The aim of the research was to determine the ultrastructure of the cells of the muscle wall of the mice gallbladder under the influence of ursodeoxycholic acid. Materials and methods. The animals were divided into 2 groups: experimental (n = 17) - mice which received ursodeoxycholic acid at a dose of 100.0 mg/kg and control (n = 13) - intact ones (distilled water). Histological and ultrastructural analyses of gallbladder wall samples of mice were performed. Results. Mitotic figures of myocytes in the wall of the gallbladder bottom (1.794 ± 0.103 %) and body (1.607 ± 0.095 %) in the experimental group of mice were significantly more frequent compared to the controls (0.946 ± 0.058 % and 0.873 ± 0.061 %) (p < 0.01). Enhancing nuclear activity of fibroblasts due to chromatin decondensation and an increase in the number of nuclear pores were observed after the action of ursodeoxycholic acid (0.106 ± 0.007 vs. 0.253 ± 0.018) (p < 0.01). A considerable increase in the number of interstitial cells of Cajal in the muscular membrane of the bottom and body of the gallbladder was noted after the injection of ursodeoxycholic acid (4.61 ± 0.37 mm-2 vs. 2.77 ± 0.23 mm-2) (p < 0.01). Conclusions. Our hypothesis was confirmed by the presence of histological signs of leiomyocyte hyperplasia and an increase in the nuclear activity of fibroblasts in the muscle wall of the mice gallbladder as a result of ursodeoxycholic acid use. Excessive activation of hyperplastic processes of leiomyocytes has an unsettled nature after the injection of ursodeoxycholic acid. An increase in apoptosis of smooth myocytes is observed under the influence of ursodeoxycholic acid. Stimulation of gallbladder wall motility with ursodeoxycholic acid might be associated with an increase in the number of interstitial cells of Cajal in the muscular membrane of the bottom and body of the gallbladder.